Sensory processing associated with subcategories of restricted and repetitive behaviors in Japanese children and adolescents with autism spectrum disorder - Noda, Haruka; Yoneda, Naoto; Kamogawa, Ken; Tanaka, Goro; Ide, Masakazu; Iwanaga, Ryoichiro (Frontiers in Child and Adolescent Psychiatry, 2024)
Background Restricted and repetitive behavior (RRB) is a core symptom of autism spectrum disorder (ASD). The structure of RRB subcategories and their relationship with atypical sensory processing in Japan are not well understood. This study examined subcategories of the RRB in Japanese children with ASD and explored their relationship with sensory processing. Methods A total of 103 children and adolescents with ASD participated in this study, with more than 70% having a co-occurring intellectual disability. First, exploratory factor analysis of the RRB items of the Social Responsiveness Scale second edition (SRS-2) was conducted to identify RRB subcategories. Second, Spearman correlation and multiple regression analysis were run to examine relationships between the RRB subcategories of SRS-2 and subsections of the Short Sensory Profile. Results Exploratory factor analysis indicated a two factors solution; repetitive sensory and motor behavior and insistence on sameness. Multiple regression analysis suggested that Movement Sensitivity and Auditory Filtering were associated with insistence on sameness. Furthermore, Underresponsive/Seeks Sensation, Visual/Auditory Sensitivity, and diagnosis of intellectual disabilities were associated with repetitive sensory and motor behavior. Conclusions Findings indicate that RRB subcategories are differently related to sensory processing patterns in children with ASD. These results suggested that RRB subcategories are beneficial to consider the relationship between RRB and sensory processing.